Omnichannel Marketing Strategies and Their Impact on Online Purchase Decisions - Wijaya, Steven; Mahendra, IGN Andhika (International Conference of Innovation and Community Engagement, 2025)
The rapid advancement of digital technologies has led to the emergence of omnichannel marketing as a dominant approach in modern retail. This research examines how integrated marketing strategies across various online and offline channels influence consumer decision-making in online purchases. Utilizing the Technology Acceptance Model (TAM) and consumer behavior theories, this study employs a quantitative approach with survey data collected from 350 respondents who have experienced omnichannel retail environments. Key variables analyzed include channel consistency, cross-platform personalization, and seamless user experience. The findings indicate that consistency in messaging and ease of transitioning between channels significantly enhance consumers’ perceived convenience and trust, ultimately leading to stronger purchase intentions. Moreover, personalization across touchpoints and real-time responsiveness further amplify the effectiveness of omnichannel strategies. This study contributes to the literature on digital commerce by offering empirical evidence on how strategically aligned channel integration improves customer satisfaction and purchase behavior. The insights are particularly valuable for businesses aiming to optimize customer journeys in a competitive e-commerce landscape.